Evaluation of denture hygiene among removable denture wearers referred to clinics of Kerman, Iran - Molouk Torabi Parizi; Shahrzad Taheri; Parviz Amini; Marzieh Karimi Afshar; Mehrnaz Karimi Afshar (Journal of Oral Health and Oral Epidemiology, 2013)
BACKGROUND AND AIM: The number of patients who need prosthetic treatments has increased. Efficient and regular procedures for cleaning removable dentures are important for maintaining good oral health. The aim of this study was to analyze the oral and prostheses care habits of removable denture users, who attended the clinics of Kerman, Iran.